Focused Differential Glycan Analysis with the Platform Antibody-assisted Lectin Profiling for Glycan-related Biomarker Verification - Kuno, Atsushi; Kato, Yukinari; Matsuda, Atsushi; Kaneko, Mika Kato; Ito, Hiromi; Amano, Koh; Chiba, Yasunori; Narimatsu, Hisashi; Hirabayashi, Jun (Molecular & cellular proteomics, 2009)
Protein glycosylation is a critical subject attracting increasing attention in the field of proteomics as it is expected to play a key role in the investigation of histological and diagnostic biomarkers. In this context, an enormous number of glycoproteins have now been nominated as disease-related biomarkers. However, there is no appropriate strategy in the current proteome platform to qualify such marker candidate molecules, which relates their specific expression to particular diseases. Here, we present a new practical system for focused differential glycan analysis in terms of antibody-assisted lectin profiling (ALP). In the developed procedure, (i) a target protein is enriched from clinic samples (e.g. tissue extracts, cell supernatants, or sera) by immunoprecipitation with a specific antibody recognizing a core protein moiety; (ii) the target glycoprotein is quantified by immunoblotting using the same antibody used in (i); and (iii) glycosylation difference is analyzed by means of antibody-overlay lectin microarray, an application technique of an emerging glycan profiling microarray. As model glycoproteins having either N-linked or O-linked glycans, prostate-specific antigen or podoplanin, respectively, were subjected to systematic ALP analysis. As a result, specific signals corresponding to the target glycoprotein glycans were obtained at a sub-picomole level with the aid of specific antibodies, whereby disease-specific or tissue-specific glycosylation changes could be observed in a rapid, reproducible, and high-throughput manner. Thus, the established system should provide a powerful pipeline in support of on-going efforts in glyco-biomarker discovery.